ANALISIS FOREIGN DIRECT INVESTMENT (FDI) INDONESIA DI NIGERIA PERIODE 2014—2017: STUDI KASUS PT. INDOFOOD SUKSES MAKMUR* - Fitri , Chaerunisa (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
Liberalism in international trading opens the opportunity for any country to sell their products to the whole world. One of the activities that cannot be separated from international trading is Foreign Direct Investment (FDI). Nigeria is one of many countries which really welcome the concept of FDI. There are Indonesian corporations that have been investing in Nigeria, one of them is PT. Indofood Sukses Makmur. With the Toleram Group from Singapore, the company has built a new corporation together, called De United Foods Industries Ltd (DUFIL). FDI concept and Product Life Cycle (PLC) theory are used in this research, along with the qualitative method and descriptive technique of data analysis. The result shows that PT. Indofood Sukses Makmur (De United Foods Industries Ltd) is a company with horizontal FDI model. The company classified in greenfield FDI category, which developed with merger. According to PLC theory, instant noodle from PT. Indofood Sukses Makmur which has been produced by De United Foods Industries Ltd in Nigeria is currently in the mature step.